EFFECT OF COMBINED THYROXINE AND CORTISOL TREATMENT ON HATCHING OF EGGS, POST-EMBRYONIC GROWTH AND SURVIVAL OF LARVAE OF HETEROPNEUSTES FOSSILIS - Nayak, P. K.; Mishra, T. K.; Mishra, J.; Pandey, A K. (Journal of Indian Fisheries Association, 2015)
In order to record the effects of thyroxine and cortisol (individual/combined) on hatching, post-embryonic growth and survival of larvae ofHeteropneustes fossilis, newly fertilized eggs were given bath immersiontreatments of L-thyroxine (T4; 0.05 mgfl), cortisol (0.50 mgll) and T4+ cortisol(0.05 mgll +0.50 mgfl) for 15 days. Hatching of eggs, growth and survival of thelarvae improved significantly (P < 0.001) in the hormone treated groups ascompared to those of control. The frequency of deformities was reduced inthe combined hormone treatment group. The present observations suggestthat the advanced digestive function probably induced by T4+cortisoltreatment might have resulted in improvement in food utilization during thecritical phases of first feeding and promoted vital developmental processesresulting in uniform growth, decreased mortality, better survival andtransformation of larvae to juveniles. This combined hormone therapy appearsto have practical utility in fish hatchery practice for better success in larvalrearing.Keywords: Thyroxine (T4), cortisol, larvae, survival, growth,Heteropneustesfossilis